2008
DOI: 10.1097/tp.0b013e31816dd64a
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustive Differentiation of Alloreactive CD8+ T Cells: Critical for Determination of Graft Acceptance or Rejection

Abstract: The rapid and extensive initial activation and differentiation of donor-reactive CD8+ T cells that occurs after liver transplantation leads to clonal exhaustion or deletion of the alloreactive CD8+ T-cell repertoire resulting in spontaneous tolerance induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 45 publications
2
44
1
Order By: Relevance
“…The potential antiapoptotic action of B7-H4 on islet cells raises the potential malignant transformation induced by ectopic overexpression of B7-H4. B7-H4 has been observed to be overexpressed in various cancers, such as breast, ovarian, and pancreatic cancers, suggesting that B7-H4 overexpression might associate with epithelial cell transformation (39,40). So, although B7-H4 gene transfer may on one hand enhance ␤-cell survival, it may also result in transformation (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…The potential antiapoptotic action of B7-H4 on islet cells raises the potential malignant transformation induced by ectopic overexpression of B7-H4. B7-H4 has been observed to be overexpressed in various cancers, such as breast, ovarian, and pancreatic cancers, suggesting that B7-H4 overexpression might associate with epithelial cell transformation (39,40). So, although B7-H4 gene transfer may on one hand enhance ␤-cell survival, it may also result in transformation (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Several groups have reported on the impact of alloantigen load on alloreactive CD8+ T cells and demonstrated evidence of T cell exhaustion with decreased proliferative capacity and reduced effector cytokine production (Quezada et al, 2003; Steger et al, 2008). However, the expression of coinhibitory molecules was not examined in these studies.…”
Section: T Cell Exhaustion Negative Costimulation and Transplantationmentioning
confidence: 99%
“…In the case of transplantation, the relationship between the mass of donor tissue transplanted and rejection or acceptance has previously been demonstrated in a study [43] showing that simultaneous transplantation of two kidneys and two hearts resulted in long-term graft acceptance, whereas single allogeneic heart and kidney graft were rejected acutely. Another study [35 ▪▪ ] extended these observations and demonstrated that CD8 + T-cell exhaustion followed by deletion of the alloreactive T-cell repertoire was responsible for prolonged liver allograft survival compared with smaller-sized heart and kidney transplantation. Similarly, utilizing islet, skin and heart transplant models, it was demonstrated that a threshold T-cell frequency is required to mediate rejection [44], that a low ratio of T-cell frequency to donor tissue mass is a critical determinant of donor-specific hyporesponsiveness and graft survival [45] and that low- frequency donor-specific T-cell responses are regulated by the PD-1 pathway [46].…”
Section: Factors Affecting T-cell Exhaustionmentioning
confidence: 98%
“…A more direct evidence of T-cell exhaustion in transplantation was provided by an elegant study [35 ▪▪ ] that demonstrated that a rapid and extensive activation and proliferation of the donor-reactive CD8 + T cells in the initial period after liver transplantation was followed by CD8 + T-cell exhaustion characterized by unresponsiveness and deletion of the alloreactive T-cell repertoire. The most direct evidence for T-cell exhaustion in transplantation was provided recently in a model of chronic allograft rejection [36 ▪ ] in which fucosyltransferase-VII–deficient ( Fut7 −/− ) recipients, with impaired selectin-dependent leukocyte recruitment, exhibited long-term graft survival with minimal vasculopathy compared with wild-type controls.…”
Section: Evidence For T-cell Exhaustion In Transplantationmentioning
confidence: 99%